1988
DOI: 10.1111/j.1365-2141.1988.tb02433.x
|View full text |Cite
|
Sign up to set email alerts
|

The syndrome of abnormal chromatin clumping in leucocytes: a myelodysplastic disorder with proliferative features?

Abstract: Five patients presenting extremely exaggerated chromatin clumping in leucocytes, associated with a loss of segmentation, are described. Peripheral cytopenia, a high percentage of circulating immature granulocytes (chiefly myelocytes) with variable leucocytosis, marrow hypercellularity with granulocytic hyperplasia and moderate dysplastic changes in erythroblastic and megakaryocytic lines, constitute, together with the granulocytic nuclear anomaly, the characteristic features of the studied cases. Cytogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 13 publications
1
12
0
3
Order By: Relevance
“…Similar observations have also been made in chronic myeloid leukemia with involvement of 17p in the blast phase [31]. Another pathologic feature of the granulocytic series is clumping of the nuclear chromatin, which has been associated with a deletion of the short arm of chro mosome 12 [32].…”
Section: Certain Anomalies Do Have Clinical and Morphological Correlasupporting
confidence: 61%
“…Similar observations have also been made in chronic myeloid leukemia with involvement of 17p in the blast phase [31]. Another pathologic feature of the granulocytic series is clumping of the nuclear chromatin, which has been associated with a deletion of the short arm of chro mosome 12 [32].…”
Section: Certain Anomalies Do Have Clinical and Morphological Correlasupporting
confidence: 61%
“…The 'syndrome of abnormal chromatin clumping' [17][18][19][20] can be considered as a variant of aCML. 10 In most patients, the WBC count is increased, but occasional patients may have normal values.…”
Section: Mds/mpn: Main Entitiesmentioning
confidence: 99%
“…Survival times are similar to those reported in aCML. 10,[17][18][19][20] Chronic myelomonocytic leukemia CMML is a MDS/MPN whose typical manifestation is its peripheral blood monocytosis. 12,[21][22][23][24][25] The incidence of CMML is approximately three cases per 100 000 individuals older than 60 years.…”
Section: Mds/mpn: Main Entitiesmentioning
confidence: 99%
“…About 20% of blasts were positive for CD15 and CD33. A diagnosis of secondary acute myeloid leukemia (FAB type M1) evolving from myelodysplasia, with abnormal chromatin clumping syndrome 16 was made. Cytogenetic studies of bone marrow and peripheral blood specimens showed a complex aberrant karyotype: 42−43,XX,del(1)(q42), −5, del(7)(q21), add(9)(p22), −12, −16, −17, add(17)(q25), del(18)(q21), −20, +1−2 mar.…”
Section: Clinical Details Of Patient Kgmentioning
confidence: 99%